METODE KONVENSIONAL DAN INKONVENSIONAL DALAM PEMBELAJARAN BAHASA ARAB - Sahkholid Nasution (Jurnal Ilmiah Didaktika, 2012)
In the Arabic language learning, the method has a very significant position to achieve the goal. If so, then the method must exist on each of the learning process conducted by a teacher or educator. Method is a comprehensive plan to provide a systematic presentation of the language specified approach. Even the method is considered as art in the transfer of knowledge/learning materials to students and is considered more significant than aspects of the matter itself. Arabic language learning methods are manifold, both conventional (traditional) or modern character (innovative). Arabic language learning success also depends on how the educators (teachers) choose the appropriate method of learning. Even educators may need to make changes or replacement methods in the learning process in line with changing attitudes and interests of students to the material presented.